Utilization of Waste Dust from Asphalt Concrete Manufacturing as a Sustainable Subbase Course Material in Pavement Structures - Salisa Chaiyaput; Pimchanok Sertsoongnern; Jiratchaya Ayawanna (My University, 2022)
High calcium waste dust from asphalt concrete manufacturing was utilized to stabilize low-quality lateritic soil as a subbase course material in road structures. Asphalt waste dust up to 30 percent by weight (wt%) was incorporated into the solely lateritic soil and the mixture of lateritic soil containing 5 wt% Portland cement. The asphalt waste dust was successfully used as a subbase course material in road structures according to the standard specifications of pavement materials issued by the Thailand Department of Highways. The minimum 20 wt% asphalt waste dust induced a sufficiently high California bearing ratio, optimized plastic index, liquid limit, and swelling index of soil above the minimum standard requirements for a subbase course material. The fine particles of asphalt waste dust showed filler-like properties to reduce the voids and generated a very dense surface in the stabilized lateritic soil samples. With the small content of cement mixes, a decrease in the calcite phase in the soil stabilized with asphalt waste dust indicated a partial promotion of CaCO3 from the asphalt waste dust in the cement hydration reaction. The very high strength (CBR > 250%) of these stabilized soil samples approached the standard for base course material (CBR ≥ 80%), which was beyond the expectation for the subbase material (CBR ≥ 25%). Thus, recycling-waste dust from asphalt concrete manufacturing can be used as an effectively sustainable subbase course and base course materials in further generation for road construction purposes.
Keywords: Subbase; California bearing ratio; Base course; Wearing course; Filler (materials); Asphalt concrete; Geotechnical and construction materials studies